Way of the Cross as the Metaphor of Evanescence - Bednarczyk, Monika (Starość i młodość w literaturze i kulturze, 2016)
Way of the Cross contains the last moments of Jesus’s life. It begins with the judgment and ends whenthe body is entombed.This story of Jesus’s death can also be seen like a picture that shows human’s life. Existential problemsare written in Way of the Cross next to religious because of particular God’s presence in human being.The evanescence is one of those issues, which are analysed by the authors of reflections fulfilling structureof 14 episodes that create Jesus way to Calvary.The idea of this article is to show and analyse the examples of consideration the death and mourningtaken from contemporary Way of the Cross texts. The analysis of them leads to conclusion that humanlooks for a confrontation with the picture of evanescence. This experience helps people to understandtheir nature which nowadays is displaced by society.